Feasibility of radiosurgery dosimetry using NIPAM 3D dosimeters and x-ray CT. (August 2019) - Adamson, Justus; Carroll, Jaclyn; Trager, Michael; Yoon, Paul; Kodra, Jacob; Yin, Fang-Fang; Maynard, Evan; Hilts, Michelle; Oldham, Mark; Jirasik, Andrew
Abstract: We investigated the feasibility of using N-isopropylacrylamide (NIPAM) dosimeters with x-ray CT to verify radiosurgery dose. Dosimeters were prepared at one facility and shipped to a second facility for irradiation. A simulation CT was acquired and plans prepared for a 4 field box, and a 4 arc VMAT radiosurgery plan to 6 targets with 1cm diameter. Each dosimeter was aligned via CBCT and irradiated, followed by 5 diagnostic CTs acquired after >24 hours, which were averaged for analysis. Absolute dose calibration was applied and dose evaluated for both plans. Hounsfield Units were proportional to dose above 10-12Gy. For the 4-field box, mean difference between measured and predicted dose >10Gy was -0.13Gy ±1.69Gy and gamma index was <1 for 72% and 65% of voxels using a 5% / 1mm and 3% / 2mm criteria, respectively (threshold = 15Gy, global dose criteria). For the multifocal SRS case, mean dose within each target was within -0.14Gy± 0.55Gy of the expected value, and gamma index was < 1 for 94.0% and 99.5% of voxels, respectively (threshold = 15Gy). NIPAM based 3D dosimetry with x-ray CT is well suited for validating radiosurgery spatial alignment, as well as dose distributions when dose is above 10-12Gy.